A quality improvement collaborative increased preventive education and screening rates for women at high-risk for type 2 diabetes mellitus in primary care settings - Lorenz, Allison (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2020)
• Successfully implemented a QI initiative to change primary care practice workflows. • Effectively identified women aged 18–44years at high risk for type 2 diabetes. • Increased provision of preventive education for women at-risk for T2DM. • Improved completion rate of clinically recommended T2DM screenings.